La mediación penal y su admisibilidad para los delitos cometidos mediante los medios de comunicación social. - Esparza Aguirre, Diego Fernando (2013)
The importance and transcendency of the problem partner - juridical of the penal mediation and their admissibility for the crimes made by means of the social media, he/she is founded mainly in the Art. 190 of the Constitution of the Republic of the Ecuador that it recognizes the arbitration, the mediation and other alternative procedures for the solution of conflicts, with subjection to the law, in matters in those that for their nature you can tolerate, this disposition authorizes to the parts involved in a conflict, to follow a process and to undergo the alternative means of solution of conflicts, what has allowed that you can consent in civil matter, however in penal matter it is not applicable, since expressed norm that allows to the parts to be welcomed to the penal mediation to solve the conflict that has injured the very juridical one that is the right to the secret of the communications, and that entire crime made by means of the social media that you/they are subjected to special procedures according to the normative one doesn't exist effective of the Code of Penal Procedure that consists starting from the Art. 383 until the Art. 389; where he/she settles down for the juzgamiento of the crimes made by means of the printing, the broadcasting, the television and other social media, the general norms of this Code will be applied. It also points out as responsible the Director, Editor, owner or responsible for a means of communication, these will respond for the infraction that is judged and against them the cause will be continued, to the non manifestaren, when the District attorney requires it, the author's name, reproducer or responsible for the communication. Therefore, he/she forces the Directors to remit the District attorney it requires it, the films, the videotapes or the recordings of sounds. Of not making it, the process will be continued against them. That is to say, the penal procedure to be continued would be either according to the penal action that belongs the crime, of public or private action, however with the new tendencies of the alternative means of solution of conflicts it becomes necessary to be welcomed to the penal mediation. The theoretical work and of field of the present thesis it allowed me to obtain approaches, with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of objectives, and contrastación of the outlined hypotheses, allowing to support the proposed changes. The content of the thesis is an intellectual effort of the postulante in the scientific and methodological environment that approaches theoretical and empirically, the admissibility to the penal mediation the crimes made by social media.